Alkali ions pre-intercalation of δ-MnO2 nanosheets for high-capacity and stable Zn-ion battery. (March 2022) - Xie, Qixing; Cheng, Gao; Xue, Tong; Huang, Leheng; Chen, Shihong; Sun, Yue; Sun, Ming; Wang, Haozhi; Yu, Lin
Abstract: Manganese oxide is regarded as the most promising cathode material for aqueous zinc-ion batteries (ZIBs). However, the practical application of Mn-based ZIBs has been restricted by slow diffusion kinetics of Zn ions and unstable structure of MnO2 . Herein, δ-MnO2 nanosheets with a layered structure are pre-intercalated with various alkali cations (X-δ-MnO2, X = Li +, Na +, or K + ) and are designed for ZIBs to understand the effect of cations on the electrochemical behavior and charge storage mechanism of the δ-MnO2 cathode. It demonstrates that the cycling stability, the rate capability, and the reversibility of X-δ-MnO2 are improved with the sequence of K-δ-MnO2 > Na-δ-MnO2 > Li-δ-MnO2 owing to the increase of pre-intercalated ion radius. Furthermore, H + intercalation followed by Zn 2+ mechanism has been verified by observation of the two distinct voltage platforms with a reversible deposition/dissolution of Zn4 SO4 (OH)6 ·4H2 O. This study confirms that the pre-intercalation of the alkali cation is an efficient strategy to improve the energy storage performance and to understand the charge-discharge mechanism of δ-MnO2 for ZIBs. Graphical abstract: Image 1 Highlights: Li +, Na +, or K + is pre-intercalated into δ-MnO2 via a one-step synthetic route. K-δ-MnO2 provides the largest lattice space and the best Zn 2+ storage performance. The charge-discharge mechanism of K-δ-MnO2 is revealed.